2011
DOI: 10.4012/dmj.2010-142
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding silica to zirconia to counteract zirconia’s tendency to degrade at low temperatures

Abstract: Yttria-based zirconia material (Y-TZP) widely used in dentistry, may degrade in a humid, low-temperature environment such as that in the oral cavity. The aim of this study was to compare the degradation of a new silica doped Y-TZP material with that of conventional Y-TZP by using accelerated aging tests at 200°C. The results of the accelerated tests revealed that after 50 hours of aging, the conventional Y-TZP samples had damaged surfaces that were weakened by 50 to 60%, while the silica-doped Y-TZP samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
(26 reference statements)
0
18
0
3
Order By: Relevance
“…Hence, the importance of the grain size factor is highlighted: larger tetragonal grain size leads to a lower stability to phase transformation. 21,22 Despite not causing deleterious effects on the mechanical performance, the evaluated aging regimens promoted an extensive increase in m-phase content and had a small influence on surface roughness (Table). The storage and the mechanical cycling regimens led to lower m-phase content, and resulted in a limited effect on roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the importance of the grain size factor is highlighted: larger tetragonal grain size leads to a lower stability to phase transformation. 21,22 Despite not causing deleterious effects on the mechanical performance, the evaluated aging regimens promoted an extensive increase in m-phase content and had a small influence on surface roughness (Table). The storage and the mechanical cycling regimens led to lower m-phase content, and resulted in a limited effect on roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Even when the ambient temperature is low, the crystals degrade due to phase transformation to the monoclinic phase in the presence of atmospheric moisture. Thus, a marked decrease in mechanical strength is a concern regarding Y-TZP 34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…As for the comparison of the results, the accelerated aging test at 200°C and 2 bar in this experiment was used as the same condition as our former experiment 7) . It is reported that an accelerated aging test performed for one hour at 134°C and 2 bar is equivalent to 3 to 4 years of service in the 37°C intravital environment 19) .…”
Section: Discussionmentioning
confidence: 99%
“…The aging group specimens were immersed in distilled water inside a decomposition vessel consisting of an inner Teflon tube and an outer stainless tube. They were all subjected to an accelerated aging test for 5 h at 200°C and 2 bar using a drying oven (MOV-112, SANYO, Moriguchi, Japan) 7) . Each coping specimen was secured to the titanium abutment with resin cement (SA Luting, Kuraray Medical, Tokyo, Japan).…”
Section: Accelerated Aging Test and Facture Loadmentioning
confidence: 99%
See 1 more Smart Citation